Modelling future impacts of urban development in Kuwait with the use of ABM and GIS. Issue 1 (1st August 2017) - Alghais, Nayef; Pullar, David
Abstract: During the last six decades, Kuwait has experienced rapid and unprecedented population growth with only a small increase in the urban areas. The alarming rise in urban density in Kuwait has caused issues for the residents' lifestyles, the economy and the environment. These issues have been aggravated by urban planning which perpetuated a city‐centric urban form without modelling the impacts of current patterns of urban growth. A spatial model using Agent Based Modelling (ABM) and Geographical Information Systems (GIS) is proposed to model disaggregate future changes in land‐use patterns given forecast population estimates and planning policies. The two main impacts considered are housing shortage and traffic congestion, as these are the two most significant social impacts for Kuwaitis. This article discusses the design methodology and parameterization of the ABM and the agent groups. It characterizes urban growth by rules for different citizen groups, historical growth patterns and the influence of decision‐makers. The model is validated against data for the period 1995‐2015 and simulations run to 2050; the results predict that continued city‐centric growth will aggravate the problems, with more than 50% increase in housing shortage and congestion unless the government intervenes to rectify the situation.